PERFORMANCE ANALYSIS OF AGENT BASED DISTRIBUTED DEFENSE MECHANISMS AGAINST DDOS ATTACKS - Singh, Karanbir; Singh Dhindsa, Kanwalvir; Bhushan, Bharat (International Journal of Computing, 2018)
The current internet infrastructure is susceptible to distributed denial of service (DDoS) attacks and has no built in mechanism to defend against them. The research on these kinds of attacks and their defense is significant for the security and reliability of the internet. We have already proposed a collaborative agent based distributed DDoS defense scheme which detect and prevents against DDoS attacks in ISP (Internet Service Provider) boundaries. The actual task of defense is carried out by agents and coordinators in each ISP. The defense system works by inspecting incoming traffic on edge router and identify the happening of DDoS attacks. The agent’s implements an entropy-threshold based detection algorithm. The coordinators share attack related information with neighboring ISPs in order to achieve distributed defense. The performance of defense system is evaluated on the basis of some identified metrics. The effectiveness of the defense system is evaluated in the presence and absence of defense system. The result indicates that the proposed defense system does accurate attack detection with very few false positives and false negatives.